Pengembangan Modul Pembelajaran Berbasis Kearifan Lokal pada Mata Kuliah Keterampilan Menulis dan Membaca SD - Toding Bua, Mety; Ady Saputra (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2023)
The learning module was developed because there was no teaching material in the form of a module based on local wisdom developed by the course lecturer. Therefore, through this research, it is expected to develop a learning module based on local wisdom. This research aims to develop a learning module suitable for use in teaching and to assess students' responses to the development of the learning module. They provide varied teaching materials to facilitate students' teaching and learning processes. This module was developed as a product through the Research and Development (RnD) method with the development process using the 4-D model (Define, Design, Develop, and Disseminate stages). Data collection instruments consist of validation sheets and questionnaires. The validation sheet is used to assess the validity of the product. The questionnaires are used to assess students' responses to the development of the interactive module. This research showed the feasibility of the research results in terms of validation by subject matter experts and language experts. The validation results of the material expert reached 88.57%, with a very feasible category. Meanwhile, the language expert validation results reached 93.33%, with a very feasible category. The survey results on students' interest in using the module reached 92.67%, with a very interested category. Based on the results, the learning module developed for elementary school reading and writing skills is highly suitable and attractive for teaching and learning.